What is the optimal postoperative oral feeding timing protocol for thoracotomy patients? Prospective randomized clinical trial on postoperative complications - YILDIZELİ, BEDRETTİN; AKOĞLU, HALDUN; BATIREL, HASAN FEVZİ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2017)
Background: This study aims to determine the optimal postoperative oral feeding initiating time with the lowest postoperative pulmonary complication rate in thoracotomy patients and compare cardiac and psychiatric complication rates caused by different feeding schemes. Methods: The study included 107 consecutive patients (84 males, 23 females; mean age 53.9 years; range 17 to 81 years) planned to undergo lung resection via elective thoracotomy for both benign and malignant pathologies in a single institution during a time period of two years. Patients were prospectively randomized into three groups according to postoperative oral intake initiation time: oral intake was initiated on the postoperative sixth hour in group 1, 24th hour in group 2, and when bowel functions resumed in group 3. Groups were then compared in terms of postoperative complication rates. Results: Groups were homogenous according to demographic properties. Twenty patients (18.7%) developed postoperative pulmonary complications: four (11.1%) in group 1, eight (22.2%) in each of groups 2 and 3. Median oral intake initiation time for group 3 was 47 hours (range 27 to 82 hours). There was no significant difference between the groups in terms of postoperative pulmonary and cardiac complications (p=0.358 and p=0.175, respectively). While postoperative incidence of delirium was significantly increased in group 3 (n=5, 14.3%, p=0.032), it was not observed in group 1 and it was observed in two patients (5.6%) in group 2. This complication was directly correlated with development of postoperative pulmonary complications (odds ratio=14.2; p=0.002). Conclusion: Early (sixth hour) initiation of postoperative oral feeding is not related with increased pulmonary complications. On the contrary, early initiation may enable rapid recovery of postoperative mental and physical conditions, prevent psychiatric disorders, and reduce pulmonary complication rates. Thus this scheme can be administrated safely in all thoracotomy patients without potential risk for preoperative aspiration.
Keywords: Aspiration; complications; dietary management; pulmonary; thoracotomy; PNEUMONIA; SURGERY; NAUSEA